Objectivity from a Phenomenological Point of View: An Analytical Study (Latakia University Journal - Arts and Humanities Sciences Series, 2015)
The purpose of this article is to examine the possibility of immediate against mediated or theoretical knowledge. However, in both types of knowledge, there is a face toface confrontation. I encounter something which I wish to apprehend. Therefore, aspirationalready assumes a duality, a gulf between me and that which faces me. The object is, as itwere, already there, autonomous, present as a fact. This is, of course, a basic tenet ofpositivism and empiricism. The world as summation of all its possible contents is simply'given'. This article also tries to enquire a little further into this perspective, questioning thenature of this objectivity exploring possible ambiguities. I shall be looking mostly atKantian transcendentalism and Husserlian and Merleapontian phenomenology.